ATP boosts lit state formation and activity of Arabidopsis cryptochrome 2. (27th August 2018) - Eckel, Maike; Steinchen, Wieland; Batschauer, Alfred
Summary: Cryptochrome (cry) blue light photoreceptors have important roles in the regulation of plant development. Their photocycle includes redox changes of their flavin adenine dinucleotide (FAD) chromophore, which is fully oxidised in the dark state and semi‐reduced in the signalling‐active lit state. The two Arabidopsis thaliana cryptochromes, cry1 and cry2, and the plant‐type cryptochrome CPH1 from Chlamydomonas rheinhardtii bind ATP and other nucleotides. Binding of ATP affects the photocycle of these photoreceptors and causes structural alterations. However, the exact regions that undergo structural changes have not been defined, and most importantly it is not known whether ATP binding affects the biological activity of these photoreceptors in planta . Here we present studies on the effect of ATP on Arabidopsis cry2. Recombinant cry2 protein showed a high affinity for ATP ( K D of 1.09 ± 0.48 μm ). Binding of ATP and other adenines promoted photoreduction of the FAD chromophore in vitro and caused structural changes, particularly in α‐helix 21 which links the photosensory domain with the C‐terminal extension. The constructed cry2 Y399A mutant was unable to bind ATP and did not show enhancement of photoreduction by ATP. When this mutant gene was expressed in Arabidopsis null cry2 mutant plants it retained some biological activity, which was, however, lower than that of the wild type. Our results indicate that binding of ATP to cry2, and most likely to other plant‐type cryptochromes, is not essential but boosts the formation of the signalling state and biological activity. Significance Statement: Binding of ATP by plant cryptochromes enhances signalling state formation, but how this affects the biological activity of these blue light photoreceptors was unknown. Here we show that a mutant of Arabidopsis thaliana cry2, which is unable to bind ATP, is still biologically active but to a smaller degree than the wild‐type photoreceptor. Thus, binding of ATP to cry2 in vivo is relevant for its biological function.